2019
DOI: 10.1155/2019/5823219
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity ofApisspp. in Thailand Inferred from 28S rRNA Nuclear and Cytochrome b Mitochondrial Gene Sequences

Abstract: Knowledge of the genetic diversity of Apis spp. is important in order to provide a better understanding of breeding strategies that relate to the conservation of wild species and colony survival of farmed species. Here, honeybees of five Apis species were collected from 12 provinces throughout Thailand. After DNA extraction, 28S rRNA nuclear (710 bp) and cytochrome b (cytb) mitochondrial (520 bp) gene fragments were sequenced. Homologous sequences (nucleotide identity of over 95%) were obtained from GeneBank u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…The Jukes-Cantor genetic distances based on the VG gene sequences between the northern and southern populations of A. cerana varied from 0.005 to 0.015 (the average was 0.010) (Table S4). In comparison, the Jukes-Cantor genetic distance was 0.018 between subspecies of A. mellifera (A. m. carnica, A. m. ligustica, A. m. sicula, A. m. iberica, A. m. adami, A. m. macedonica, A. m. anatoliaca, A. m. syriaca, A. m. intermissa) based on the COX1 gene of mtDNA [28]; was 0.17 between 2 honey bee species (A. mellifera, A. cerana) based on complete mtDNA [29]; varied from 0.001 to 0.014 between subspecies of A. cerana; varied from 0.075 to 0.081 between species A. mellifera and A. cerana based on the VG gene of nDNA [8]; was 0.033 between 15 species of Anastrepha based on the COX1 gene of mtDNA [30]; and varied from 0.002 to 0.039 within species and from 0.074 to 0.131 between 5 species of Apis based on the CYTB gene of mtDNA [31]. Thus, the Jukes-Cantor genetic distances based on the VG gene sequences between A. cerana populations from similar climatic conditions is half that between A. cerana populations from different climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The Jukes-Cantor genetic distances based on the VG gene sequences between the northern and southern populations of A. cerana varied from 0.005 to 0.015 (the average was 0.010) (Table S4). In comparison, the Jukes-Cantor genetic distance was 0.018 between subspecies of A. mellifera (A. m. carnica, A. m. ligustica, A. m. sicula, A. m. iberica, A. m. adami, A. m. macedonica, A. m. anatoliaca, A. m. syriaca, A. m. intermissa) based on the COX1 gene of mtDNA [28]; was 0.17 between 2 honey bee species (A. mellifera, A. cerana) based on complete mtDNA [29]; varied from 0.001 to 0.014 between subspecies of A. cerana; varied from 0.075 to 0.081 between species A. mellifera and A. cerana based on the VG gene of nDNA [8]; was 0.033 between 15 species of Anastrepha based on the COX1 gene of mtDNA [30]; and varied from 0.002 to 0.039 within species and from 0.074 to 0.131 between 5 species of Apis based on the CYTB gene of mtDNA [31]. Thus, the Jukes-Cantor genetic distances based on the VG gene sequences between A. cerana populations from similar climatic conditions is half that between A. cerana populations from different climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain more support values for the nodes on the phylogenetic trees (Wortley et al, 2005), combination markers are suggested and this was supported by Aman-Zuki et al (2019) who had proven that by combining mitochondrial and nuclear datasets, more robust phylogeny of the parasitic wasp, the Apanteles group was observed. In addition, Meemongkolkiat et al (2019) and Baird et al (2017) also presented more resolved phylogeography and phylogeny in both species of study by implementing nuclear and mtDNA.…”
Section: P R E S Smentioning
confidence: 99%